2020
DOI: 10.3390/ph13070154
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase Inhibition Activity of Coumarin Derivatives—QSAR and Molecular Docking Study

Abstract: Lipoxygenases (LOXs) are a family of enzymes found in plants, mammals, and microorganisms. In animals and plants, the enzyme has the capability for the peroxidation of unsaturated fatty acids. Although LOXs participate in the plant defense system, the enzyme’s metabolites can have numerous negative effects on human health. Therefore, many types of research are searching for compounds that can inhibit LOXs. The best quantitative structure–activity relationship (QSAR) model was obtained using a Genetic Algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…In the work of Lončarić et al [ 39 ], it was also observed that substitution at position 6 of the coumarin scaffold with a bromine group led to potent soybean lipoxygenase inhibition. However, according to the molecular docking studies, the compounds of this study have interactions with the binding site of human lipoxygenase (5-LOX, in complex with arachidonic acid (PDB code: 3V99)) and soybean LOX (soybean LOX-3 in complex with (−)-epigallocatechin gallate ((−)-EGCG) (PDB code: 1JNQ)).…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Lončarić et al [ 39 ], it was also observed that substitution at position 6 of the coumarin scaffold with a bromine group led to potent soybean lipoxygenase inhibition. However, according to the molecular docking studies, the compounds of this study have interactions with the binding site of human lipoxygenase (5-LOX, in complex with arachidonic acid (PDB code: 3V99)) and soybean LOX (soybean LOX-3 in complex with (−)-epigallocatechin gallate ((−)-EGCG) (PDB code: 1JNQ)).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic algorithm is a general-purpose optimization and search technique which is based on the evolutionary process of natural selection. Genetic algorithm permits the individuals of a population to evolve under certain specific selection rules to a condition that maximizes the fitness function [ 32 ]. The PyMOL Molecular Graphics (Version 1.8.4.0, Schrödinger, LLC) was used for the visualizations and graphics generations [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Coumarin has been classified as an oxygenated heterocycle rather than a benzoic acid derivative. Many coumarin hybrids have been reported to be used for medical disorders, namely as anti-allergic [ 103 ], antiviral [ 104 ], vasodilatory [ 105 ], antibacterial [ 106 , 107 ], exhibiting cyclooxygenase inhibition [ 108 ], lipoxygenase [ 109 ], antithrombotic [ 110 ], and anticancer activity [ 111 ]. The molecular hybridization of the coumarin nucleus to a biodynamic system that is a biologically active pharmacophore has enhanced biological activities.…”
Section: Coumarin Hybridsmentioning
confidence: 99%